New Caledonia crows use tools for non-foraging activities - Wimpenny, J; Weir, A; Kacelnik, A (Springer-Verlag, 2011)
Tool use is of great interest for cognitive research, largely because it can be particularly revealing about the underlying information processing mechanisms. Tool use that is inflexible or requires extensive experience to change, and that is only addressed towards specific targets such as food, is not likely to reflect unusual or particularly complex cognition. On the contrary, if tools are exployed flexibly and for a variety of innovative purposes, then conventional combinations of inherited predispositions and associative learning are challenged and interesting questions emerge. Since New Caledonian crows (Corvus moneduloides) are especially adept at using and making tools for food extraction, we decided to examine their ability to generalise this to other contexts. We recorded how five pairs of New Caledonian crows interacted with novel objects that were not associated with food. We observed eight occasions in which the first contact with the novel object was mediated by a tool, suggesting that the function of the tool was for exploration. This is the first report of non-foraging tool use in New Caledonian crows, and it implies that the cognitive operations controlling tool-oriented behaviour in this species are more general than previously thought.